Penguatan Literasi Digital dan Komunikasi Etis Berbasis Kader PKK sebagai Model Pemberdayaan Masyarakat Era Digital - Prastowo, Mahisa Dwi; Fikri, Luthfy Rijalul (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
The development of digital technology has brought significant changes to patterns of public communication, including at the level of local communities. On the other hand, low levels of digital literacy have the potential to generate various social problems, such as the spread of hoaxes, communication conflicts, and unethical communication practices. Unlike most digital literacy programs that primarily focus on the technical aspects of media use, this Community Service Program (Pengabdian kepada Masyarakat) adopts an approach that emphasizes strengthening the social role of PKK cadres as community communicators and digital literacy agents. This program aims to enhance digital literacy and ethical communication capacities among women PKK cadres in Kedaung Village through a participatory approach that integrates digital literacy training, reflective discussions based on local experiences, and contextual digital information verification practices. The novelty of this program lies in the integration of digital literacy, communication ethics, and the social functions of PKK cadres, resulting in a sustainable community-based empowerment model. The results indicate a significant improvement in participants’ understanding of digital literacy, their ability to verify information, and their awareness of ethical communication in digital spaces. Moreover, PKK cadres not only became beneficiaries of the program but also transformed into active agents driving digital literacy within their families and communities. These findings affirm that strengthening digital literacy through community social roles is an effective and adaptive strategy for fostering a healthy, participatory, and ethical digital communication culture in the digital era.